A formação leitora da criança amazônida: um estudo da prática de leitura na educação infantil em uma escola no município de Tabatinga - Lima, Jeillyanne Figueiredo de (Brasil, 2024)
The present research, entitled “The reading formation of Amazonian children: a study of reading practice in Early Childhood Education in a school in the city of Tabatinga-AM” has the general objective of analyzing reading practices in early childhood education as a possibility for the development of children's reading training in preschool. Analyzing how educators participate in this process. Initially, it can be considered, taking into account bibliographical research, and teachers are partners in this process of training readers, however they need to be effectively involved with education so that they can contribute significantly to the training of readers. This is qualitative research, of a scientific nature, which aims to present descriptions, reflections and analyses, aiming to understand the importance of reading in preschool, aiming at the teaching and learning process of children in Early Childhood Education. The reflections are based on the studies Kramer (1996, p.18), Mota (2016, p.37), Coelho (2000, p. 30) among others that deal with the object of the research. It is also based on the laws that support early childhood education National Common Curricular Base (2017), RCA, RCNEI, BNCC, PNE In the research, interviews and observations were used during the internship to collect data, seeking information necessary to achieve fundamental answers with the subjects of Erly childhood education research, favoring the achievement of the study objective and contact with reality for a better understanding of reading practices and as a way of advancing the child's teaching-learning process in the classroom. The results show that reading is fundamental for the development of children's learning, as it is a way of promoting learning through pleasurable, interactive and meaningful experiences, using children's stories as pedagogical tools.